Nurses’ clinical practices reducing the impact of HIV-related stigmatisation in non-HIV-specialised healthcare settings: a protocol for a realist synthesis - Pelletier, Jérôme; Bergeron, Dave; Rouleau, Geneviève; Guillaumie, Laurence (BMJ open, 2022)
IntroductionDespite tremendous progress in care, people living with HIV (PLHIV) continue to experience HIV-related stigmatisation by nurses in non-HIV-specialised healthcare settings. This has consequences for the health of PLHIV and the spread of the virus. In the province of Quebec (Canada), only four interventions aimed at reducing the impact of HIV-related stigmatisation by nurses have been implemented since the beginning of the HIV pandemic. While mentoring and persuasion could be promising strategies, expression of fears of HIV could have deleterious effects on nurses’ attitudes towards PLHIV. In literature reviews on stigma reduction interventions, the contextual elements in which these interventions have been implemented is not considered. In order to develop new interventions, we need to understand how the mechanisms (M) by which interventions (I) interact with contexts (C) produce their outcomes (O).Methods and analysisRealist synthesis (RS) was selected to formulate a programme theory that will rely on CIMO configuration to describe (1) nursing practices that may influence stigmatisation experiences by PLHIV in non-HIV-specialised healthcare settings, and (2) interventions that may promote the adoption of such practices by nurses. The RS will draw on the steps recommended by Pawson: clarify the scope of the review; search for evidence; appraise primary studies and extract data; synthesise evidence and draw conclusions. To allow an acute interpretation of the disparities between HIV-related stigmatisation experiences depending on people’s serological status, an initial version of the programme theory will be formulated from data gathered from scientific and grey literature, and then consolidated through realist interviews with various stakeholders (PLHIV, nurses, community workers and researchers).Ethics and disseminationEthical approval for realist interviews will be sought following the initial programme theory design. We intend to share the final programme theory with intervention developers via scientific publications and recommendations to community organisations that counter HIV-related stigmatisation.